Kh. Abdul Karim Jamak: His Tiological Perspective on Qada' and Qadar in the Digital Era at Kerinci Regency - Jambi - Ahmad Zuhdi; Fakhri Yusuf; Marwan Marwan (Dinasti International Journal of Education Management And Social Science, 2024)
This article explains the theme "Kh. Abdul Karim Jamak: His Tiological Perspective on Qada' and Qadar of the Digital Era in Kerinci Regency - Jambi". It is known that indeed Qadar is the secret of Allah towards His creatures. About what God explains to man, man can know and believe it. And what he does not know, then man accepts and trusts him. Without anyone arguing against Allah regarding His perfect Work and wisdom. Accepting and believing in qada and qadar in the digital information era which is full of modern and sophisticated knowledge, Muslims should have intelligence in mastering digital technology, to answer challenges and challenges that want to damage the pure values of Islamic teachings. Through the way and approach of Kh. Abdul Karim Jamak expounding the Islamic principles of qada and qadar can help instill confidence that no matter how intelligent humans are assisted by science and technology, the qadar and qadar of Allah Almighty will still happen. Among examples are when earthquakes, floods and tsunamis occur, lightning and so on that cannot be detected by existing technological tools. To answer the question that arises for the current generation, it is necessary to refer to the thoughts of one of the scholars which in this case is the thought of Kh. Abdul Karim Jamak, adapted to the Quran and Sunnah.